Nascent entrepreneurship and the level of economic development - Sander Wennekers; André J. van Stel; A. Roy Thurik; Paul Reynolds (Max Planck Institute for Research into Economic Systems, 2005)
Based upon two strands of literature, this paper hypothesizes a U-shaped relationship between a country's rate of entrepreneurial dynamics and its level of economic development. This would imply a different scope for entrepreneurship policy across subsequent stages of development. Regressing GEM's 2002 data for nascent entrepreneurship in 36 countries on the level of economic development as measured either by per capita income or by an index for innovative capacity, we find support for a U-shaped relationship. Testing our results against several control variables, evidence is again found for this relationship with economic development, in addition to significant effects of the business ownership rate (+), social security expenditure (-), aggregate taxes (+) and population growth (+). The results suggest that a 'natural rate' of nascent entrepreneurship is to some extent governed by 'laws' related to the level of economic development. For the most advanced nations, improving incentive structures for business start-ups and promoting the commercial exploitation of scientific findings offer the most promising approach for public policy. Developing nations, however, may be better off pursuing the exploitation of scale economies, fostering foreign direct investment and promoting management education.
Keywords: L16; J23; O11; M13; 330; Nascent entrepreneurship; economic development; Unternehmer; Unternehmensgründung; Entwicklung; Entwicklungsindikator; Vergleich; Welt